Developing a strategic framework to optimize the performance of Zimbabwe’s elite men’s football team in international competition - Chirara, Admire (BUSE, 2023)
The ultimate objective of the research was to develop a strategic framework that would optimise the performance of Zimbabwe's men's national football team in international games. The problem is that the Zimbabwe National Elite football team has a track record of delivering unrivaled outcomes at the international level, which is compounded by a need for more literature in the context of Zimbabwe Football optimisation to inform practice. Thus, the research was driven by a desire to solve practical and theoretical shortcomings discovered in the management of Zimbabwe's successful football team. The study made use of the ideas generated through qualitative and quantitative approaches. This research adopted the concurrent mixed-methods research design involving collecting both quantitative and qualitative data at the same time. Therefore, the collection of quantitative and qualitative data was independent of each other, and one type of data is not informing the collection of the other type of data. Thematic analysis for data gathered using semi-structured interviews was performed using the NVivo 12 software. Quantitative Data obtained from the questionnaires was analyzed using SPSS software version 20. The results show that the Zimbabwe National team lacked a consistent and reliable source of talent to assure the team's competitiveness at the International level. The present framework perpetuates the existing unfavourable opinions of Zimbabwe's Senior Football Team as stagnant and deteriorating. This has resulted in the departure of major players, coaches, and cooperate sponsors. The study recommends that the Zimbabwe Football Association should provide suitable conditions for players to develop their Physical Demands, Technical Demands, and Psycho-Social Demands in order for their performances to meet international practice. The study further recommends that the Zimbabwe Football Association should start a normative data collection that would control talent in local leagues and also generate the tools for talent development in Zimbabwe. The Zimbabwe Football Association is urged to construct high-performance facilities where it can train players from an early age.
Keywords: Sports frameworks; National Football teams; International competitions; Football